PENYULUHAN PENTINGNYA HYGINE DAN SANITASI DALAM MENCEGAH INFEKSI STH SERTA IDENTIFIKASI STH PADA KUKU WARGA DI KECAMATAN TRAGAH - Norma Farizah Fahmi; Dwi Aprilia Anggraini (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Personal hygiene comes from the Greek, derived from the word 'personal' which means individual and 'hygiene' which means healthy. Personal hygiene is an action to maintain the cleanliness and health of a person for both physical and psychological well-being. Types of personal hygiene include skin, foot, hand and nail hygiene, hair care, oral and dental care, eye, ear and nose care. The purpose of personal hygiene care is to improve one's health status, maintain one's personal hygiene, improve personal hygiene that is lacking, prevent disease, increase one's self-confidence and create beauty. One disease that is quite closely related to personal hygiene is worms and fungal infections (mycosis). In rural communities where the majority of the population work as farmers who are directly in close contact with the soil which is the breeding medium for STH, of course, personal hygiene is very necessary so that they are not easily infected with STH. Another thing that needs to be considered is the environmental conditions in the community in the village, namely the distance between the house and the stables for livestock such as cows which are very close together. The close distance between the house and the livestock cage also has the potential to transmit parasites if the livestock feces are not cleaned regularly. Based on these conditions, it is necessary to conduct counseling on personal hygiene and environmental sanitation in the community as well as identify the presence of worm infection in nail samples in villagers which on this occasion will take place in Tragah District. There were 26 participants identified with STH infection and 14 participants not identified with STH infection